RESEARCH OF MULTIPLE INVESTMENT STRATEGIES USING A SHORT AND LONG POSITION (International Journal of Innovative Technologies in Economy, 2019)
The construction of an optimal portfolio of securities is one of the main tasks of managing the financial system, in which individual assets are only a component part. However, each asset also requires a separate study.I gave the article building an investment portfolio with a zero strategy, comprising borrowing some assets and buying other assets for the same amount. The study comprised choosing the length of the historical horizon, the ranking criterion and the portfolio structure that ensured the maximum investor income.